Teaching entrepreneurship in Portugal and some critical reflections (Research, Society and Development, 2022)
In this article, I aim to present the idea of entrepreneurial intention and contextualize the situation of teaching entrepreneurship in Portugal. With this general objective in mind, I seek to demonstrate, through bibliographic research, the institutional and legal bases and guidelines that promote the teaching of entrepreneurship in the European Union, as well as I seek to highlight some of the initiatives and projects related to the theme of entrepreneurial education in Portugal. Finally, I propose a brief reflection on entrepreneurial education in order to critically debate the relevance of such an approach and its implications as an educational project at European and Portuguese levels.